Development of discovery learning-based student worksheets to facilitate mathematical understanding in geometric transformation - Fariyani, Sri Aisyah; Yuanita, Putri; Suanto, Elfis (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study addresses the issue of students' low mathematical understanding ability, which is a crucial competency in mathematics learning. In response, the research aims to develop a discovery learning-based student worksheet on the topic of geometric transformations to support meaningful learning for Grade XI high school students. The study adopts a Research and Development (R&D) approach using the ADDIE development model, consisting of the stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, validation procedures, and worksheet trials. The research involved six students from Class XI-B MIPA at Al-Muslimun Senior High School during the implementation stage. Two main instruments were employed: a validation sheet to assess the validity of the worksheet and a student response questionnaire to evaluate its practicality. The results showed that the developed worksheet achieved a very valid category with an average score of 3.61 and a very practical classification in small-group trials, with an average score of 89.16. These findings indicate that the developed student worksheet meets the criteria of both validity and practicality, making it a potential alternative learning resource in mathematics education.